Lesson study in competence development of accounting teachers - Imam Hasan; Trisno Martono; Susilaningsih Susilaningsih (Jurnal Pendidikan Vokasi, 2018)
This research aimed to find out and explore the lesson study practice in developing the accounting teacher's professionalism. This research employed qualitative research using a single instrumental case-study strategy. The data were collected using in-depth interview, observation, and documentation. Then, they were analysed using interactive model. The results of the research showed that with the implementation of the lesson study in schools, it succeeded in improving the four teachers' competencies. The improvement of the pedagogical competence can be seen from the well preparation of learning, the selection of teaching strategies according to the characteristics of the students and the implementation of memorable learning for the students. Professional competence can also be seen from the teacher's preparation in choosing relevant and up-to-date materials, teaching them by connecting to daily practice and always evaluating the material taught to maintain the quality of the material. The improvement of the social competence can be seen from the more effective communication between the teachers and students and their colleagues. The improvement of the personality competence is indicated by the teachers' attitudes that are increasingly wise and prestigious in responding to the conditions related to their work. The research implication is that the practice of lesson study can form accounting teacher learning groups that serve as a place for sharing and discussion in developing their professionalism.